EFEKTIVITAS BAHAN AJAR TEMATIK TERINTEGRASI KEARIFAN LOKAL KHOMBOW UNTUK MENINGKATKAN HASIL BELAJAR SISWA SELOLAH DASAR DI KECAMATAN SENTANI TIMUR KABUPATEN JAYAPURA - Ali, Aisyah; Sukmawati; Elieser Kulimbang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims assess the effectiveness of thematic teaching materials based on local wisdom “Khombouw” in improving the learning outcomes of elementary school students. These teaching materials are designed based on local cultural values to provide contextual and relevant learning experiences. The research method used was a quasi-experiment with a pretest-posttest nonequivalent control group design. The research subjects were 42 fourth grade students from two elementary schools, namely SD YPK Asei and SD Inpres Yoboi. The results of data analysis showed that the experimental group using “Khombouw”-based teaching materials had a significant increase in learning outcomes compared to the control group using conventional teaching materials (p < 0.05). This finding confirms that the integration of local wisdom in learning not only supports academic understanding but also strengthens students' cultural identity. In addition, the Discovery Learning model used helps students in exploring cultural values in an active and participatory manner. This research recommends the development of local wisdom-based teaching materials as a strategic approach to improving the quality of education in Indonesia, especially in areas with strong local cultural wealth.